Trends and prospects of pulses and implications for nutrition - Chand, Ramesh; Sharan, Shambhavi (The Indian Journal of Genetics and Plant Breeding, 2017)
The ratio of per capita availability of cereals and pulses has changed from 1: 0.152 during 1961-1965 to 1: 0.108 during 2011-2013. This implies that for every kg of cereals consumed in the country, the amount of pulses consumed has reduced to 71 per cent during the last fifty years. The decline in status of pulses production has distorted the dietary balance, aggravating the already existing under nutrition and malnutrition. Through this paper we try to explore the causes for the slow growth in the production of pulses and its role in the Indian agrarian economy. We also try to understand whether the changes in dietary balance have been voluntary or forced by availability. Lastly, we try to investigate whether pulses help in addressing the issues of under nutrition and malnutrition in the country, or should we be complacent with food security based on rice and wheat alone.